Małżeńskie prawo osobowe ustawodawstw porozbiorowych obowiązujących w Rzeczypospolitej Polskiej w dwudziestoleciu międzywojennym - Stawecka-Firlej, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The aim of the study is to identify various systems of matrimonial law in force in the territory of the Republic of Poland in the interwar period; in the central, southern and western provinces. There were five different systems of matrimonial law in the area of the Republic of Poland, however the most important of them: the law on marriage of 16 March 1836 — in force in the territory of the former Polish Kingdom, Austrian Civil Code ABGB of 1811 — in force in the territory of the former Austrian partition and German Civil Code BGB of 1896 — in force in the territory of the former Prussian partition, were discussed in this article.The different institutions of the personal matrimonial law, taking into account the regulations of individual legal systems concerning betrothal, marriage and its effects, dissolution of the marriageor married life, and the impact of the effects of divorce and separation on the legal relationship between spouses, were described in the article.The main aim was to compare the matrimonial law having a strictly religious nature Polish Kingdom with the law, in which the principles of the canon law were in force as the rules of civil law, however the church law was taken into account only to a very limited extent ABGB, and with the law, in which the institution of marriage was only a public institution BGB.
Keywords: Civil Code of Austria; Civil Code of Germany; Kingdom of Poland; marriage law; the interwar period